The effect of soil particle arrangement on shear strength behavior of silty sand - Nik Daud, Nik Norsyahariati; Kam, Ru Hui; Abd. Ghafar Azmi, Juliana (EDP Sciences, 2015)
The presence of fines in sandy soil is recognized as a problem in geotechnical engineering. It is often assumed that the strength and liquefaction potential of a soil decreases with increasing fines content. Sand with a significant amount of fines is always encountered in geotechnical engineering projects. The main interest of this paper is to study the effect of particles arrangement and stress behaviour on sand and silty sand sample. The objectives are to determine the basic properties as well as the morphological and mineralogical properties and the relationship of those properties to the stress behaviour of the soils. Sand-silt mixtures with fines contents of 20% and 40% were prepared and a series of testing was carried out to determine their basic properties, morphological and thin section properties, and mechanical properties by using direct shear box equipment. Results show that the basic properties and morphological properties of soil affect the mechanical behaviour of soil. Shape of the soil particle can influence the packing of the soil, hence altering the mechanical behaviour of the soil. From the thin section, the soil is observed to be well graded and have a dense packing while the minerals observed were mainly quartz and rutile.